2020
DOI: 10.5539/ijel.v10n2p357
|View full text |Cite
|
Sign up to set email alerts
|

Error Analysis in the Written Compositions of EFL Students: A Classroom Study

Abstract: The aim of the study is to analyse the linguistic errors in the writings of EFL students in a Saudi university. For error analysis, the writing tasks of a group of students were collected and analysed. The results showed that the frequently committed errors were at the sentential level as well as the word level. The most frequent errors were the errors of spellings and the least were the errors of demonstratives. The marked errors were categorised as errors of omission, addition, misinformation and misordering… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 4 publications
0
9
0
2
Order By: Relevance
“…Lexico-grammatical errors are common in these people's writing and prevent them from producing good-quality compositions (Luo & Liao, 2015). Many studies have investigated the linguistic errors made by EFL learners and have found that, when writing, EFL learners make both grammatical and lexical errors (Chaudhary & Al Zahrani, 2020;Karazoun, 2016;Lahuerta, 2018;Nuruzzaman et al, 2018;Sermsook et al, 2017;Zülal, 2020).…”
Section: Grammatical and Lexical Accuracy In Efl Learners' Writingmentioning
confidence: 99%
“…Lexico-grammatical errors are common in these people's writing and prevent them from producing good-quality compositions (Luo & Liao, 2015). Many studies have investigated the linguistic errors made by EFL learners and have found that, when writing, EFL learners make both grammatical and lexical errors (Chaudhary & Al Zahrani, 2020;Karazoun, 2016;Lahuerta, 2018;Nuruzzaman et al, 2018;Sermsook et al, 2017;Zülal, 2020).…”
Section: Grammatical and Lexical Accuracy In Efl Learners' Writingmentioning
confidence: 99%
“…(1) In terms of grammatical errors, the employment of verb groups accounted for 58 percent, owing to verb group confusion when dealing with English grammar systems. (2) e presentation of distinct senses consumed 38 percent of the content mistake type, which was caused by a failure to choose acceptable words owing to a lack of vocabulary competence.…”
Section: Samplementioning
confidence: 99%
“…e grammatical model, for instance, concentrates on the language side of translation [1,2]. e cultural model, on the other hand, stresses the communicative side of translation, whereas the interpretative model focuses the pragmatic aspect of translation.…”
Section: Introductionmentioning
confidence: 99%
“…Students who are less proficient in the mentioned areas may give little concern to the writing section. Chaudhary & Zahrani (2020) also mentioned that motivating second language learners on the importance of writing skills is challenging despite knowing that good writing skills would benefit them professionally.…”
Section: Introductionmentioning
confidence: 99%